TALAK TIGA DI LUAR PENGADILAN PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF BAGI PEGAWAI NEGERI SIPIL (Studi Analisis Putusan Pengadilan Agama ArgamakmurNomor 0207/Pdt.G/2015/PA.AGM) - Jayanti, Hepi Duri (UIN Fatmawati Sukarno Bengkulu, 2018)
In the case number 0207 / Pdt.G / 2015 / PA.AGM, it is known that a husband who has a government employees status has directly uttered Talak 3 to his wife, after that, he applied for divorce to the religious court Argamakmur without attach- ing permission of divorce from superiors. Furthermore, reading the verdict of the judges of the Argamakmur Religious Court who granted the petition for divorce of the Petitioner, but did not include the fact that the Petitioner had dropped Talak 3 to his wife before the husband applied for divorce to the Religious Court and did not attach the divorce permit from his superior. While it is clear that there is a legal difference between the Talak 1 and the Talak 3. In addition, the absence of a divorce permit from the competent authority will result in the Petitioner being punished with severe discipline based on the discipline regula- tions of civil servants. Based on the above background, this research reveals two issues, namely first how is the legal power of Talak 3 appellation according to Islamic law and positive law. Second, what is the benefit of divorce certificate for government employees who filed for divorce in Religious Court? This type of research is normative juridical research or library research which is then described descriptively. The results of this study conclude that the legal power of Talak 3 appellation outside the courts according to Islamic law is valid. Because in Islamic law (the Qur’an and hadith) no one arranges if divorce should be pronounced in court. Even Talak does not need a witness when the husband said it; Talak also can be spoken by husband and firmly or with satire language. But the cancellation of divorce cannot be done as well as Talak 3 without going through Talak1 and Talak 2. Whereas according to Law Number 1 Year 1974, the appellation of divorce must be done in front of the court, otherwise the divorce is not legally recognized by the state. And among the husband and wife are still legally bound state even though according to Islamic law is not husband and wife anymore. While divorce permits from government employees superi- ors only can be used by the government employees who seek divorce to a religious court. The benefit of the divorce permits for the government employees is to avoid disciplinary punishment in accordance with applicable provisions. Then if the divorce request has not been submitted to a religious court, then the government employees concerned may be strived for peace by the team or direct superior, so the process of divorce proceedings is not necessary, this means saving time and money. If the divorce proceedings continue, the divorce papers can be useful as a basis for judicial consideration in the judgment, as the divorce papers are the result of a team’s recommendation that examines the reasons for divorce to obtain a divorce certificate for the government employees